(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study explores the dynamics of a magnetohydrodynamic viscoelastic fluid flowing past a vertically moving porous plate, accounting for variable temperature, radiation effects, chemical reactions, and concentration. The governing mathematical formulation is rigorously examined through perturbation analysis. The primary objective of this research is to investigate the impact of various parameters and dimensionless numbers on the fluid flow, thermal boundary, and concentration profiles. An increase in the magnetic parameter leads to a reduction in the velocity profile due to the opposing Lorentz force. Elevated thermal radiation results in an increased temperature profile, while a stronger chemical reaction and higher Schmidt number lead to a decrease in the concentration distribution. The Schmidt number, which characterizes molecular momentum and mass transfer, plays a pivotal role in multiphase flows by influencing boundary layers and diffusion.